Komunitas Radio Amatir sebagai Agen Mitigasi Bencana: Sosialisasi dan Pelatihan Penggunaan APAR - Wiryajati, I Ketut; Adnyani, Ida Ayu Sri; Putra, I Ketut Perdana; Joniarta, I Wayan; Maryati, Sri (Jurnal Gema Ngabdi, 2025)
The amateur radio community plays a strategic role in emergency communication, especially when conventional networks are disrupted during disasters. However, fire preparedness within this group remains limited. Fire risks mainly arise from electrical failures, short circuits due to non-standard equipment, and excessive heat from transmission devices. A lack of awareness regarding fire safety procedures, including the use of fire extinguishers (APAR), heightens vulnerability. This program aimed to improve fire preparedness among amateur radio operators in Mataram City through awareness campaigns and APAR training. The methods included observation, risk analysis, training development, implementation, and evaluation. Results revealed significant improvements in knowledge and practical skills, despite gaps in routine inspections and evacuation planning. The program strengthens the community's role not only as an emergency communication provider but also as an active fire mitigation agent, contributing to a safer and more resilient environment.